Neopsittaconirmus vendulae, a new species of louse (Phthiraptera: Philopteridae) from the Cockatiel Nymphicus hollandicus (Psittaciformes: Cacatuidae) - Sychra, Oldãich (Zootaxa, 2006)
A new species of Neopsittaconirmus Conci is described from lice collected from captive cockatiels Nymphicus hollandicus, in Australia, Czech Republic, and Germany. This is the first record of lice from this host. These captive birds probably originated from limited populations which were randomly selected from wild populations and then bred and transported by cage-bird breeders. Keys are provided for identification of the 27 species of Neopsittaconirmus.